Failure analysis of austenitic stainless steel pipes in amine liquid regeneration unit of a desulfurizer. (November 2015) - Sui, Rongjuan; Liu, Yan; Wang, Weiqiang; Qu, Yanpeng; Su, Chenggong; Chang, Feng
Abstract: Failure investigation was carried out on the austenitic stainless steel pipes of an amine liquid purification unit. The authors investigated the causes of the pipe failure by analyzing chemical compositions of materials and corrosion products, observing microstructures, and testing the pitting corrosion resistance of materials. The results showed that the failure was caused by pitting corrosion due to the presence of chlorine ions in the working medium. Another important cause of pitting corrosion was the decrease of corrosion resistance of welds owing to the microstructural changes taken place during welding. A large amount of sulfate ions in the working medium accelerated the pits growth. At the same time, proposals were put forward to the user of the failure pipes. Highlights: The failure of pipes taken place at weld joints is caused by pitting corrosion. Pitting corrosion is induced by chlorine ions and accelerated by sulfate ions. Microstructural changes caused by welding decrease the corrosion resistance of weld.